Educational Tycoon Game and Cultural Heritage: Developing PAANTU BANG: Pasar Hantu Bangka - Amsana Rachmani, Almeera; Syahputra, Razen; Darmawan, Okki; Prayuda Wardani, Hastina; Amsana Rachmanio, Goldy; Faruq Vista, Umar (Journal of Games, Game Art, and Gamification, 2025)
With the rapid development of technology and digital information, video games have become a significant cultural phenomenon, with a rapidly growing number of players each year. Concerns regarding the impact of video games on mental health have been largely dismissed by recent studies, suggesting minimal negative effects and emphasizing the motivational aspects of gaming. Recognizing the potential of video games as educational tools, this study explores the development of "PAANTU BANG: Pasar Hantu Bangka," a cultural tycoon game created by VAR Production, a team from the Bangka Belitung Islands. Utilizing the prototyping method for software development, the game combines business management principles with local cultural heritage. Through stages of requirement gathering, design, prototype building, evaluation, and revision, the game was successfully developed and published. The game offers players practical insights into running a business, including resource management and financial planning, while also educating them about regional folklore and traditional dishes. The result is a unique educational tool that effectively integrates entertainment with learning, promoting both business acumen and cultural awareness.